2017
DOI: 10.1002/adsc.201700716
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Bioreduction of β‐Activated Vinylphosphonate Derivatives Using Ene‐Reductases

Abstract: A series of functionalized α‐chiral phosphonates was obtained by enzymatic reduction of the corresponding β‐activated vinylphosphonate derivatives employing several ene‐reductases of the Old Yellow Enzyme family as biocatalysts. The insufficient activation of the phosphonate group alone was compensated by introduction of an electron‐withdrawing group at the β‐position, which resulted in high levels of conversion (up to >99%). All active enzymes consistently furnished (R)‐configurated products with exquisite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Interestingly, a deuterium labelling study of OYE3 with the phosphonate substrate containing a cyano group at R 3 showed the EWG was exclusively the cyano group, supporting the assumption that the phosphoryl moiety is too weak to serve as an effective EWG for OYEs. Overall, the study found the most successful biocatalyst was OYE3 from S. cerevisiae , generating β-keto-, cyano- and ester phosphonates from the equivalent ( E )-isomers of α,β-unsaturated phosphonates (≤ 72% isolated yield) with high enantiopurity (> 99% ee ) 56…”
Section: Individual and Cascading Biocatalytic Reactionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, a deuterium labelling study of OYE3 with the phosphonate substrate containing a cyano group at R 3 showed the EWG was exclusively the cyano group, supporting the assumption that the phosphoryl moiety is too weak to serve as an effective EWG for OYEs. Overall, the study found the most successful biocatalyst was OYE3 from S. cerevisiae , generating β-keto-, cyano- and ester phosphonates from the equivalent ( E )-isomers of α,β-unsaturated phosphonates (≤ 72% isolated yield) with high enantiopurity (> 99% ee ) 56…”
Section: Individual and Cascading Biocatalytic Reactionsmentioning
confidence: 96%
“…Like 2-arylpropenoic acids, vinylphosphonate derivatives were considered to be poor substrates for OYEs due to the insufficient activation by the neighbouring phosphonate group. However, the addition of an additional electron-withdrawing group (EWG) at the β-position enabled these compounds to be substrates for OYEs in the production of α- and β-functionalised phosphonate antibiotic analogues 56. In this study, a large panel of purified ERs was screened against tri-substituted α,β-unsaturated phosphonates (Table 1 entry 2).…”
Section: Individual and Cascading Biocatalytic Reactionsmentioning
confidence: 99%
“…Synthetic applications of ene reductases are manifold and range from the preparation of profens [25][26][27] and chiralγ-amino acids [28][29][30] to the synthesis of chiral phosphonates [31] and nitroalkanes [32], precursors in the synthesis of pharmaceutically active ingredients. To further promote an off-the-shelve synthetic use of ene reductases, which can reduce the time and cost of the implementation of a biocatalytic step into a process significantly, we set out to expand the available biocatalytic toolbox [15].…”
Section: Isolated In 1932 Bymentioning
confidence: 99%
“…All the starting chemicals used were purchased from Sigma-Aldrich, TCI Chemicals, or Fluorochem. Acylphosphonates 3 were prepared according to literature procedures 2,4,5 and distilled prior to use. Similarly, bis(2,2,2-trifluoroethyl) phosphonates 4 were synthesized based on literature procedures.…”
Section: Scheme 4 Comparison Of Still-gennari and Hwe Olefination Of mentioning
confidence: 99%
“…3 Therefore, as part of our research we undertook to search for a reliable procedure for the synthesis of Z-α,β-unsaturated phosphonates (Z)-1 containing a carbonyl or ester moiety in the β-position. It should be mentioned that although the corresponding E-isomers can be easily obtained with excellent E-selectivity and in good isolated yields using the Wittig reaction, 2,4 the reports on general methods for the synthesis of the desired Z-isomers are scarce. Perusing the literature, we came across a paper of Harris and McFadden who claimed to have obtained βphosphonoacrylates with unexpectedly high Z-preference in the reaction of acylphosphonates 3 with diethoxyphosphorylacetates, as the source of α-carbanions, under the Horner-Wadsworth-Emmons (HWE) conditions.…”
mentioning
confidence: 99%